2019
DOI: 10.1177/1178636119849934
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Associations of Schistosoma mansoni Infection and Metabolic Syndromes in Humans: A Cross-Sectional Study in Northeast Ethiopia

Abstract: Background: Recent animal and retrospective human studies have demonstrated that Schistosoma mansoni infection may have potential to protect against development of metabolic syndromes. Thus, the aim of this study was to assess metabolic panel among S. mansoni egg positives and egg negatives in stool examinations. This study was a cross-sectional study, conducted involving 120 participants from S. mansoni endemic town … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 24 publications
(24 reference statements)
2
40
3
Order By: Relevance
“…Recently, the reverse relationship between schistosome infection and metabolic syndrome has received attention ( 12 , 20 ). An epidemiological study revealed that schistosome infection is negatively correlated with metabolic diseases in humans ( 26 ). Meanwhile, animal studies confirmed that chronic S. japonicum infection could improve hepatic insulin sensitivity and glucose metabolism in mice ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the reverse relationship between schistosome infection and metabolic syndrome has received attention ( 12 , 20 ). An epidemiological study revealed that schistosome infection is negatively correlated with metabolic diseases in humans ( 26 ). Meanwhile, animal studies confirmed that chronic S. japonicum infection could improve hepatic insulin sensitivity and glucose metabolism in mice ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the fourteen studies assessed, nine reported that infection with a parasitic worm had protective effects on diabetes-related parameters (26,(44)(45)(46)(47)(50)(51)(52)(53), however three studies (48,49,55) reported a positive association between specific infections and T2D diagnosis, and two studies (54,56) reported no association. Individual glucose homeostasis related outcomes are summarized in Supplementary Table 4.…”
Section: Study Findingsmentioning
confidence: 98%
“…In the host, schistosomes induce a potent T helper type 2 (Th2) ‐biased immune response and polarization of macrophages to a broad M2 phenotype, which is vital for host survival 114,115 . Interestingly, multiple epidemiological studies have observed an inverse correlation between both active infection and a previous history of schistosome infection and metabolic diseases such as obesity and diabetes, raising interest in the metabolic reprogramming that schistosomes induce in diverse cells of the immune system 105,116–119 . As one of the major players in the pathology of disease, macrophages modulate initiation and disease resolution in schistosomiasis 120 .…”
Section: Macrophage Immunometabolism In Schistosoma and Soil‐transmitmentioning
confidence: 99%